Improving Mechanical Properties of GH4169 Alloys by Reversing the Deformation and Aging Sequence. Issue 10 (22nd July 2021) - Ran, Qian; Xiang, Song; Tan, Yuanbiao
Abstract : Herein, the microstructure evolution and mechanical properties of GH4169 alloys obtained by solution treatment–deformation–two‐stage aging (SDA) and solution treatment–two‐stage aging–deformation (SAD) are investigated. The results show that the density of average geometrically necessary dislocations and the size of γ" precipitates in the SAD sample are larger than that in the SDA sample. The ultimate tensile strength (UTS) of the SAD sample is 1651 ± 24 MPa, which is 171 MPa higher than that of the SDA sample, whereas the fracture elongation of the SAD sample decreases only 3.4%. The significant increment of the UTS in the SAD samples is attributed to the contributions of the dislocation strengthening and precipitation strengthening. SAD processing could be considered as a more effective approach to enhance the mechanical properties of GH4169 alloys. Abstract : The microstructure evolution and mechanical properties of GH4169 alloys obtained by solution treatment–deformation–two‐stage aging and solution treatment–two‐stage aging–deformation are investigated. Two‐stage aging prior to deformation can result desired higher tensile property. This is attributed to the contributions of the dislocation strengthening and precipitation strengthening.